Keefektifan Teknik Bibliotherapy dan Cinemeducation terhadap Peningkatan Multicultural Awareness Siswa SMA (Jurnal Bimbingan dan Konseling Islam, 2022)
This study was conducted to determine the effectiveness of bibliotherapy and cinemeducation techniques to increase students' multicultural awareness. This study uses a single subject experimental design with multiple baseline accros subject design. Where the study subjects were given the intervention as well as a control study. there are four subjects namely LIP, CDN, MTA and DMC. In this study, using visual anaslisis chart, which consists of phases baseline, the intervention of short stories and films. Analysis carried out under conditions and circumstances beyond the baseline phase and phase baselines intervention. Results of the analysis of graph and tables on the baseline condition shows the behavior of multicultural awareness at a stable low level, but the intervention of short stories and films have increased general behavior at the level of medium after being given bibliotherapy and cinemeducation techniques. The mean change from each subject experienced an increase varied. LIP for short stories behavioral intervention by 29.25 points and 23.75 points for intervention film, while the CDN increased by 26 points for interventions of short stories and 21.25 points for intervention movies. MTA has increased by 20 points for interventions of short stories and 27 points for intervention films and DMC increased for interventions of short stories by 23.5 points and 32.5 points for intervention movies. Intervention highest to lowest short story is LIP, CDN, MTA, DMC and intervention highest to lowest films is DMC, MTA, LIP and CDN, while an increase in a given intervention technique cinemeducation bibliotherapy first followed by 25.05 points to LIP and CDN, while the increase given intervention technique bibliotherapy cinemeducation first followed by 25.75 points to MTA and DMC.